2024
DOI: 10.5603/cj.a2022.0034
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of two different definitions of contrast-associated acute kidney injury for long-term major adverse kidney events in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: Background It remains controversial whether contrast-associated acute kidney injury (CA-AKI) is associated with long-term major adverse kidney events (MAKE) in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Methods By the Acute Kidney Injury Network (AKIN) criteria, CA-AKI was defined as an increase in serum creatinine ≥ 0.3 mg/dL or 50% from baseline within 48 h after PCI; or an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…17 Cordero et al made similar observation in Spanish patients with ACS and reported the frequency of hypertension to be 68.5%. 18 AKI was developed in [23][24][25] We observed that frequency of in-hospital mortality was significantly higher in acute STEMI patients with AKI as compared to those without AKI (24.0% vs. 3.9%; p-value=0.004). When compared similar difference was noted in in-hospital mortality between acute STEMI patients with versus without AKI across various subgroups based on age, gender, BMI, diabetes, hypertension, smoking, ASA status, thrombolysis and need for PCI.…”
Section: Discussionmentioning
confidence: 99%
“…17 Cordero et al made similar observation in Spanish patients with ACS and reported the frequency of hypertension to be 68.5%. 18 AKI was developed in [23][24][25] We observed that frequency of in-hospital mortality was significantly higher in acute STEMI patients with AKI as compared to those without AKI (24.0% vs. 3.9%; p-value=0.004). When compared similar difference was noted in in-hospital mortality between acute STEMI patients with versus without AKI across various subgroups based on age, gender, BMI, diabetes, hypertension, smoking, ASA status, thrombolysis and need for PCI.…”
Section: Discussionmentioning
confidence: 99%